A randomized and double‐blind controlled trial evaluating the safety and efficacy of rituximab for warm auto‐immune hemolytic anemia in adults (the RAIHA study). Issue 1 (10th November 2016) - Michel, Marc; Terriou, Louis; Roudot‐Thoraval, Francoise; Hamidou, Mohamed; Ebbo, Mikael; Le Guenno, Guillaume; Galicier, Lionel; Audia, Sylvain; Royer, Bruno; Morin, Anne‐Sophie; Marie Michot, Jean; Jaccard, Arnaud; et al.
Abstract : This Phase 3 multicentre randomized double‐blind and placebo‐controlled trial aimed to compare the efficacy and safety of rituximab (RTX) to placebo for treating newly diagnosed warm autoimmune hemolytic anemia (wAIHA) in adults receiving prednisone. Adults with a confirmed diagnosis of wAIHA who previously received corticosteroids for less than 6 weeks could be included. At inclusion, all patients received prednisone at a daily dose of 1 mg/kg for 2 weeks, and then tapered according to a pre‐defined recommended reduction scheme. Besides prednisone, eligible patients received 2 infusions of RTX or placebo at a fixed dose of 1, 000 mg 2‐week apart. The primary endpoint was overall response rate (complete response [CR] + partial response [PR]) in an intent‐to‐treat (ITT) analysis at 1 year. A total of 32 patients (17 females [53%], mean age at inclusion 71 ± 16 years) were enrolled and randomized. In all, 27 patients were followed for at least 1 year and their data were evaluable for response. With an ITT analysis, the overall response rate at 1 year was 75% [95%CI: 47.6‐92.7] with 11 CR and 1 PR with RTX versus 31% [11.0‐58.7] (5 CR) with placebo ( P = 0.032). At 2 years, 10/16 patients with RTX versus 3/16 with placebo still showed CR ( P = 0.011). Overall, eight severe infections occurred during follow‐up, six with placebo and two with RTX ( P = 0.39). At 2 years, six patients with placebo had died, but none with RTX ( P = 0.017). Compared to placebo, RTX combined with prednisone may be effective and safe for treating newly‐diagnosed wAIHA in adults. Am. J. Hematol. 92:23–27, 2017. © 2016 Wiley Periodicals, Inc.